Synthesis of (S)-1-(2-chloroacetyl)pyrrolidine-2-carbonitrile: A key intermediate for dipeptidyl peptidase IV inhibitors - Singh, Santosh Kumar; Manne, Narendra; Pal, Manojit (Beilstein Journal of Organic Chemistry, 2008)
An alternative and practical synthesis of (S)-1-(2-chloroacetyl)pyrrolidine-2-carbonitrile was achieved. Reaction of L-proline with chloroacetyl chloride was followed by conversion of the carboxylic acid moiety of the resulting N-acylated product into the carbonitrile via the corresponding amide intermediate. The synthesized pyrrolidine derivative was utilized to prepare DPP-IV inhibitor Vildagliptin.
Keywords: amides; DPP-IV inhibitors; L-proline; N-acylation; 2(S)-cyanopyrrolidine